The confounding cosmopolitan, local action, and community college leadership: an exploration of the perceived roles, responsibilities, and best practices of urban community college leaders in addressing social equity - Jagne-Shaw, Marcel Edward (My University, 2026)
Community colleges over the next decade will be welcoming their most diverse student population ever (Callaway, 2023). Community colleges were historically designed and structurally positioned to serve student populations that are otherwise marginalized by traditional four-year universities (Mulder, 2019; O’Banion, 2019). As of 2023, approximately 10 million students were served by over 1,000 community colleges (American Association of Community Colleges [AACC]). While extensive scholarship has examined the development, evolution, and institutional outcomes of the community college sector, these institutions are not monolithic. Urban community colleges (UCC), uniquely enroll more diverse populations of students than their rural and suburban counterparts. These populations consist of more Black, Hispanic, Asian/Pacific Islander, and non-resident alien students than rural community colleges (Calaway, 2024). While community colleges generally enroll higher numbers of low-income and ethnically minoritized students than any other type of postsecondary institution, urban community colleges notably serve more diverse student demographics than their two-year peer institutions (LaGanga, 1999; Mulder, 2019). Despite their foundational mandate to support populations adversely impacted by social inequity, empirical literature remains limited regarding the overarching efficacy of these urban institutions (Smith & Miller, 2023). Research conducted by the Pew Research Center (2018) indicates that Americans are moving from rural to urban and small metropolitan counties in higher numbers than in the past. The urban population in the United States of America grew by 6.4% between 2010 and 2020 and represents 80% of the nation’s population (U.S. Census Bureau, 2022b). Moreover, the United States’ population is increasingly diversifying. The population is expected to be predominantly non-White by 2045 for the first time in history (Edgecombe, 2019). Community colleges have historically served as key access points to higher education for non-White students (Cooney and Martin, 2024). As American society continues to experience rapid diversification and urbanization (Lloyd, 2012), it is increasingly critical that community college leaders are equipped with empirical data to navigate this shifting landscape. The benefits of successfully navigating this transition will extend beyond students to ensure a robust, educated, and skilled workforce that is reflective of the diversity of the nation (Callaway, 2023). Ultimately, this research explores the perceived roles, responsibilities, and strategic approaches of executive leaders at urban community colleges in addressing and advancing social equity.
Keywords: Social equity; Executive leadership; Urban community college; Critical theory; Transformational leadership